An investigation of grading margin violation in coordinating overcurrent relay / Chan Kok Wai - Chan , Kok Wai (2018)
In a radial distribution network, overcurrent protection is commonly used to protect against faults. The overcurrent protection is achievable with the installation of a circuit breaker and an overcurrent relay with an associated current transformer at the infeed of each feeder. The overcurrent relay protection grading scheme is widely being discussed among the power system protection engineers to ensure fast yet reliable fault detection and clearance. There are currently two overcurrent relay grading methods that have been practiced in the industry to provide discrimination between the main and backup relay. One of the relay grading methods is proposed by (Hall Stephens, 1998) and the other grading method is proposed by (Ravindranath & Chander, 1977). In this research work, the two different relay grading methods practiced in the industry are presented and successfully applied for the grading of the main-backup relay pairs. The grading margin for the two methods of overcurrent relay grading methods has been investigated under the various power system dynamic scenarios such as change in load size, fault resistance, fault location, and distribution cable length. Through the short-circuit simulation in Simulink under the various power system dynamic scenarios, it was found that when using Hall’s Method to grade the relays, there are 28 cases (17.28%) in which the grading margin is below 0.3s indicating that relay grading margin is jeopardized. In contrast, when using Ravindranath’s Method to grade the relays, all calculated grading margin are 0.3 seconds and above for all the 162 cases (100%), which proved that the integrity of grading margin is secured. The theoretical findings through the simulation has been validated through real-time Hardware-in-Loop (HIL) experiment using OPAL-RT simulator. Through the HIL experiment, the generated results are similar to the results obtained from the Simulink simulation for all the main and backup relay pairs, R3-R2 and R2-R1 which are tabled in Appendix A.